SOCIETY AND ADULT DEVELOPMENT GERONTOLOGY 330 - Silverstein, Merril (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
I. Description of Purpose and GoalsThe world is undergoing a transformation in individual and population aging. In almost all countries, life expectancies are increasing rapidly, as is the proportion of the population that is elderly. In this course we investigate how the adult life course is shaped by our social context and or social relationships in conjunction with our individual characteristics. We also examine how the aging process is related to social institutions such as the family, the economy, and the political system. Additionally, we examine research in the field and analyze data using several approaches to answer questions about the social causes and consequences of aging.The course has four major goals:• To teach students how to apply basic concepts and theories in the sociology of aging and view the aging process from different disciplinary points of view.• To provide students with basic "facts" about aging, and an understanding of how these "facts" are produced by social arrangements.• To enable students to carry out several research projects using different types of data and methods to better understand the importance of social forces in aging.• To give students the opportunity to better understand themselves and others as they age in the context of a changing society.